ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN DAGING SAPI DI KOTA SURABAYA - Rusdi, Muhammad David; Suparta, Made (JEB17 : Jurnal Ekonomi dan Bisnis, 2016)
This study entitled "Analysis of Factors Affecting Demand Beef In Surabaya". The purpose of this study is going to analyze the effect of the price of beef, chicken meat prices, the gross regional domestic product (GRDP), and the total population of the demand for beef in the city of Surabaya. The types and sources of data used quantitative approach with secondary data time series observations in the period 2004-2013. The research variables consist of the dependent variable or dependent that demand for beef (QDS). Independent variables or smoking that is the price of beef (Pds), the price of chicken meat (Pda), regional gross domestic product (Y) and population (P). Data analysis tools using multiple linear regression method. Based on the results of multiple linear regression analysis of the results obtained: QDS = 1.304E7 - Pds 396 581 - 237 988 Pda + 2.345E-7 Y + 4272 P + e. Retrieved tcount beef prices amounted to 1.159, 0.263 for chicken meat prices, the gross domestic product (GDP) of 0.731 and a population of 0.119. As for the simultaneous testing of F values obtained (2.009) <F table (5.192). Thus H0 and H1 rejected. The conclusion of this study indicate that the price of beef, chicken meat prices, the gross domestic product (GDP) and population affect the demand for beef in the city of Surabaya.Keywords: Price of Beef, Chicken Meat prices, the GDP and Population